Analisis Efektivitas Biaya Penggunaan Antibiotik Pada Pasien BPJS Dengan Pneumonia Di Instalasi Rawat Inap Rumah Sakit X - Alfi Syahiroh, Wafa; Harlianti , Mariska Sri (Journal of Pharmaceutical and Sciences, 2025)
Pneumonia is a lower respiratory tract infection that remains a major challenge to public health worldwide. The use of antibiotics as primary therapy is often irrational in terms of indications, dosage, and drug selection, which can impact clinical effectiveness and treatment costs. This study aims to assess the rationality and analyze the cost-effectiveness of antibiotic therapy for BPJS patients with pneumonia in the inpatient unit of Hospital X. This study is a non-experimental study with a descriptive observational method using the payer perspective (BPJS) approach. Data were collected retrospectively from the medical records of pneumonia patients from January 2023 to June 2025. Rationality was analyzed using the 4T method. Cost-effectiveness analysis was performed using the CEA method through ACER and ICER calculations. Based on the results of the rationality evaluation, it shows that the rationality of antibiotic use based on the 4T approach includes appropriate indications (100%), appropriate drugs (100%), appropriate patients (97.7%), appropriate dose (97.1%), appropriate frequency (100%), appropriate duration (98.8%), and appropriate route (100%). The total direct medical costs of patients with cefoperazone therapy were Rp 6,073,156, while those with ceftriaxone therapy were Rp 5,474,146. The ACER value of cefoperazone was Rp 65,614 per 1% clinical effectiveness, the ACER value of ceftriaxone was Rp 57,900 per 1% clinical effectiveness, while the ICER value was Rp 866,667 per additional 1% effectiveness.